Earth Shapes and their impact on the pollution of fresh rivers, the Euphrates River within the sedimentary plain in Anbar Governorate: A case study - Hamad, Waled Hanoosh (Al-Adab Journal, 2022)
In this research, the effect of landforms on the pollution of fresh rivers within dry environments was studied, The Euphrates River was chosen in the sedimentary plain area in Anbar Governorate as a case study, as the river extends in the sedimentary plain area within its path in Anbar Governorate, and. The river is exposed to the spread of pollutants on both sides of the river within its path in the sedimentary plain area, which is one of the most serious problems that the river faces within this path. and whose harm is reflected on the person himself, until the problem of water pollution has become one of the most serious contemporary problems as it directly threatens human health. The nature of the landforms in the sedimentary plain area in Anbar Governorate has contributed greatly to the increase in the concentration of pollutants in the river water, the danger of which lies in its cumulative effect, not the effect current and instant. Which has been noticed in recent years as a result of the large number of diseases resulting from the pollution of fresh water in this environment, which requires reconsideration of the bad handling and the dumping of excessive pollutants in the fresh water environment of the Euphrates River, which has become suffering from a clear change in the physical and chemical properties or biological properties resulting from the activities of Humanity used the landforms in the sedimentary plain area in Anbar Governorate and added pollutants and polluting factors to the river environment that the Euphrates River could not get rid of at the same speed as adding them. The temperature, turbidity, electrical conductivity, and dissolved solids are among the important physical characteristics that affect the water quality of the Euphrates River, while the characteristics of pH, total hardness, the main positive and negative types, and dissolved oxygen are among the important chemical characteristics that affect the water quality of the Euphrates River within the study area.